Post-traumatic Stress Disorder With Flashbacks of an Old Childhood Memory Triggered by Right Temporal Lobe Epilepsy Surgery in Adulthood - Yrondi, Antoine; Valton, Luc; Bouilleret, Viviane; Aghakhani, Nozar; Curot, Jonathan; Birmes, Philippe Jean (Frontiers in Psychiatry, 2020)
Background A plethora of data show that the hippocampus and the amygdala are involved in post-traumatic stress disorder (PTSD). Neural dysfunctions leading to PTSD (e.g. how the amygdala and the hippocampus are altered) are only partially known. The unusual case of a patient presenting with refractory epilepsy and developing PTSD immediately after surgery is described. Such symptoms in epileptic patients may help to explore PTSD mechanisms. Case report A 41-year-old male suffering from partial refractory temporal lobe epilepsy was operated in May 2017. A right amygdala, hippocampus, and temporal pole selective resection was performed. He experienced intense PTSD symptoms 1 month after surgery. He complained about repetitive intrusive memories of abuse. The PTSD checklist score was equal to 62/80. He reported a history of childhood abuse: physical and emotional abuse as well as emotional negligence, assessed with the Childhood Trauma Questionnaire. No other medical history was recorded. He never complained about PTSD or any other psychiatric symptoms before surgery. Conclusion this case indicates that PTSD may occur after temporal lobe epilepsy surgery and may specifically stem, as in this context, from the excision of part of the medial temporal lobe structures. Although rarely reported, PTSD may be undiagnosed when not selectively detected via multi-disciplinary neurological and psychiatric management, in the preoperative period and the immediate and delayed postoperative period.